2017
DOI: 10.4103/apos.apos_49_17
|View full text |Cite
|
Sign up to set email alerts
|

E-learning and Blended Learning in Orthodontic Education

Abstract: The purpose of this article is to evaluate how effective and efficient e-learning and blended learning is when compared with traditional face-to-face learning in orthodontic education. This article also provides a comparison between face-to-face learning, e-learning, and blended learning. An open PubMed literature search was done from 1980 to 2015, and a total of 23 relevant key articles were reviewed. Information emerging from studies in orthodontic education has indicated that e-learning classes are at least… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 33 publications
0
15
0
Order By: Relevance
“…E-learning has been widely applied in medical education [ 26 , 28 30 ] and is as effective as other learning methods [ 28 , 31 ]. E-learning already plays a role in dental education, such as oral radiology [ 27 , 32 ] and orthodontics education [ 33 ]. These e-learning courses are part of compulsory curriculum oriented towards dental students only.…”
Section: Introductionmentioning
confidence: 99%
“…E-learning has been widely applied in medical education [ 26 , 28 30 ] and is as effective as other learning methods [ 28 , 31 ]. E-learning already plays a role in dental education, such as oral radiology [ 27 , 32 ] and orthodontics education [ 33 ]. These e-learning courses are part of compulsory curriculum oriented towards dental students only.…”
Section: Introductionmentioning
confidence: 99%
“…Key studies published on orthodontic education indicate that e-learning classes are at least as good and/or better than face-to-face classroom learning and blended learning is the best method. [4] A survey published in the JIOS indicates that most post graduate students suffered several concerns during their PG course. In their wish list, they indicated that lectures in PG conventions should be more focused on time management, examination preparation, national and international placement opportunities, clinical tips for future practices, and life improvement seminars.…”
Section: Emerging Trends In Postgraduate Educationmentioning
confidence: 99%
“…Considering the gap of information regarding the efficacy of smartphone-based mobile learning as an educational aid in orthodontics [ 29 ], this study aimed to compare the efficacy of traditional learning versus smartphone-based mobile learning for instruction of cephalometric landmark identification to dental students.…”
Section: Introductionmentioning
confidence: 99%